2011
DOI: 10.1055/s-0031-1286315
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cardiorespiratory and Metabolic Responses During Resistance Exercise In The Lactate Threshold Intensity

Abstract: The aims were both to determine lactate and ventilatory threshold during incremental resistance training and to analyze the acute cardiorespiratory and metabolic responses during constant-load resistance exercise at lactate threshold (LT) intensity. Ten healthy men performed 2 protocols on leg press machine. The incremental test was performed to determine the lactate and ventilatory thresholds through an algorithmic adjustment method. After 48 h, a constant-load exercise at LT intensity was executed. The inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(74 citation statements)
references
References 12 publications
6
59
1
7
Order By: Relevance
“…This indicates that these two thresholds are positively correlated such that the break points in both blood lactate concentrations and pulmonary ventilation in this exercise modality occur at a similar workload or intensity (LT: 24·8% 1RM and VT 1 : ~23·5–23·7% 1RM as determined by the algorithm adjustment method). This observation is consistent with the lack of significant differences detected by other authors between LT and VT 1 in another resistance exercise, the leg press (27·1% ± 3·7 and 30·3 ± 7·9% of 1RM, respectively) (de Sousa et al ., ). A strong relationship between LT and VT 1 has also been detected in several studies examining endurance exercise performance through GTX (Tanaka et al ., ; Aunola & Rusko, ; McLellan & Gass, ; Anderson & Rhodes, ; Burke et al ., ; Dickhuth et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This indicates that these two thresholds are positively correlated such that the break points in both blood lactate concentrations and pulmonary ventilation in this exercise modality occur at a similar workload or intensity (LT: 24·8% 1RM and VT 1 : ~23·5–23·7% 1RM as determined by the algorithm adjustment method). This observation is consistent with the lack of significant differences detected by other authors between LT and VT 1 in another resistance exercise, the leg press (27·1% ± 3·7 and 30·3 ± 7·9% of 1RM, respectively) (de Sousa et al ., ). A strong relationship between LT and VT 1 has also been detected in several studies examining endurance exercise performance through GTX (Tanaka et al ., ; Aunola & Rusko, ; McLellan & Gass, ; Anderson & Rhodes, ; Burke et al ., ; Dickhuth et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Recent investigations have examined the physiological response to resistance exercise conducted at an intensity corresponding to LT. Several authors have reported higher LT values determined in incremental LP protocols than the LT values obtained during HS exercise in our study (24·8% and 25·4% 1RM for the algorithm adjustment and visual inspection methods, respectively): 28–32·2% 1RM (Barros et al ., ), 36·6% 1RM (Oliveira et al ., ), 31·0–36·7% 1RM (Moreira et al ., ), 31·6–32·3% 1RM (Rocha et al ., ), 30% 1RM (Simões et al ., ), 23·3–31·6% 1RM (de Sousa et al ., ), 27·1% 1RM (de Sousa et al ., ), 28% 1RM (Simões et al ., ), and ~30% de 1RM (Simões et al ., ). This could be because the exercise stimulus for the HS is greater than in the LP, given the larger number of muscle groups involved as a consequence of the work of synergistic and stabilizing muscles needed to maintain the position and support the loaded barbell.…”
Section: Discussionmentioning
confidence: 99%
“…However, in most studies, ergometer exercises (Ee) traditionally are used to perform what is known as aerobic-type exercise (Sultana et al, 2012; Wang et al, 2012; Wright et al, 2012); and bars, free weights or machines are used to perform traditional anaerobic-type STe (Bloomer 2005; De Sousa et al, 2012; Mukaimoto and Ohno, 2012; Scott et al, 2011). A relevant aspect to be considered is how to match the load and intensity between STe and Ee, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Os primeiros trabalhos que adaptaram protocolos incrementais para a determinação do LAn em ER utilizaram uma razão de 1 min de esforço para 2 min de pausa entre os estágios do teste incremental 11,12 , enquanto que na presente pesquisa foi utilizada a razão 3 min para cada 1min de pausa. Apesar de outros trabalhos também terem adotado a mesma razão esforço/pausa abordada nos trabalhos originais [7][8][9][10]13,14 , a literatura sugere que quanto menor a razão esforço/pausa durante protocolos incrementais, maior a probabilidade de superestimação do LAn decorrente de uma maior eliminação dos metabólitos produzidos pelo metabolismo anaeróbio, possibilitando o alcance de cargas superiores 3,23 . Esta hipótese se confirma quando observamos que nos trabalhos em que foi utilizada a razão 1/2 (1 minuto de esforço para cada 2 minutos de repouso passivo), os voluntários alcançaram cargas próximas a 70 %1-RM durante o protocolo incremental, enquanto que na presente pesquisa, a desistência voluntária ocorreu nos estágios entre 25 e 35% de 1-RM, denotando a ocorrência de anaerobiose sob tais intensidades e impossibilitando a continuação do teste em intensidades superiores.…”
Section: Resultsunclassified
“…Neste sentido, alguns trabalhos adaptaram protocolos de cargas incrementais para a determinação do fenômeno do limiar anaeróbio (LAn) em exercícios resistidos 3,[7][8][9][10][11][12][13][14] , a fim de estimar a intensidade limítrofe entre a predominância metabólica aeróbia e anaeróbia, a qual é diretamente dependente da capacidade aeróbia do indivíduo em exercício específico 15,16 . Apesar do LAn em exercícios resistidos representar uma importante abordagem para a avaliação e prescrição de treinamento 17,18 , pouco se sabe a respeito da influência dos aspectos metodológicos sobre a determinação da intensidade do LAn 9 e principalmente, sobre importantes variáveis hemodinâmicas -como a frequência cardíaca (FC), pressão arterial sistólica (PAS) e diastólica (PAD), no decorrer do teste.…”
Section: Introductionunclassified